Temperature Dependence of Plasmaspheric Ion Composition. Issue 8 (7th August 2019) - Goldstein, J.; Gallagher, D.; Craven, P. D.; Comfort, R. H.; Genestreti, K. J.; Mouikis, C.; Spence, H.; Kurth, W.; Wygant, J.; Skoug, R. M.; Larsen, B. A.; D. Reeves, G.; et al.
Abstract: We analyze a database of Dynamics Explorer‐1 (DE‐1) Retarding Ion Mass Spectrometer densities and temperatures to yield the first explicit measure of how cold ion concentration depends on temperature. We find that cold H + and He + concentrations have very weak dependence on temperature, but cold O + ion concentration increases steeply as these ions become warmer. We demonstrate how this result can aid in analyzing composition data from other satellites without spacecraft potential mitigation, by applying the result to an example using data from the Van Allen Probes mission. Measurement of light ion concentrations above 1 electron volt (eV) are a reasonable proxy for the concentrations of colder (eV) ions. Warmer O + ion concentrations may be extrapolated to colder temperatures using our fit to the statistical distribution versus temperature. Key Points: Fractional H + and He + ion concentrations have extremely weak dependence on temperature Fractional OO + ion concentration increases with temperature For light ions, concentrations above 1 eV are a proxy for colder ions